Centering equity through in-person data collection: short report. - Zaidi, Izza; Gomez, Leonardo Dominguez; Jordan, Ashly E; Jessell, Lauren; Harocopos, Alex (Journal of Public Health, 2025)
Background During the COVID-19 pandemic, data collection activities largely became tele-remote, excluding those who did not have the required technology or digital literacy. Methods Between June and September 2020, we collected data in-person from people who use opioids in New York City. Participants were recruited via street intercept and outside four syringe service programs in the city. Surveys were conducted outdoors, with researchers and participants wearing masks and maintaining physical distance. Results A total of 329 people participated in the survey. Participants reported an average age of 45.8 years, 69.6% identified as male, 32.6% identified as Hispanic/Latino/a and 22.3% identified as Black. Many experienced unstable housing/street homelessness (65.9%) and half did not have regular smartphone access (51.1%). Conclusion Many participants were struggling to meet their basic needs and did not have the resources to participate in tele-remote research or surveillance. In-person engagement may help researchers build trust, explain data security measures, and decrease technology and comprehension barriers. As data inform policies and programs, researchers must center equity by including under-engaged groups in data collection activities.